2009
DOI: 10.1007/s11240-009-9542-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt stress on growth and osmotic regulation in Thellungiella and Arabidopsis callus

Abstract: The response of Thellungiella (Thellungiella holophila) and Arabidopsis (Arabidopsis thaliana) callus to salt stress was investigated. The relative growth rate of Arabidopsis calli decreased with increased levels of NaCl. However, the relative growth rate of Thellungiella calli increased with higher levels of NaCl, reaching maximal growth at 100 mM NaCl, but then subsequently declined. A similar pattern of accumulation of proline, glycine betaine, and total flavonoid was observed; whereas, accumulation of treh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 40 publications
6
22
1
Order By: Relevance
“…Also, Jamil et al (2007), mentioned that using NaCl at concentrations between 4.7 to 14.1 dSm -1 inhibited seed germination and seedling growth of two varieties of cabbage. Young et al (2005) and Zhao et al (2009). Also, the current results revealed a pronounced genotypic differences with regard to radical and plumule length.…”
Section: Wwwccsenetorg/jassupporting
confidence: 61%
“…Also, Jamil et al (2007), mentioned that using NaCl at concentrations between 4.7 to 14.1 dSm -1 inhibited seed germination and seedling growth of two varieties of cabbage. Young et al (2005) and Zhao et al (2009). Also, the current results revealed a pronounced genotypic differences with regard to radical and plumule length.…”
Section: Wwwccsenetorg/jassupporting
confidence: 61%
“…The level of proline accumulation continued to rise even when promotion of growth was diminished. Similarly, Zhao et al (2009) found that different salt applications increased proline levels in mangrove Thellungiella halophila. Soluble sugar also imparts osmotic regulation of the cell under salt stress (Figure 3).…”
Section: Discussionmentioning
confidence: 87%
“…Subjection of the plants to salt stress can lead to serious injury to the plants (Zhao et al, 2009;Farooq et al, 2015;Nuriyeva et al, 2016). Different techniques have been suggested to protect plants from environmental stress.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have reported the use of NaCl for in vitro salinity screening in other species of plants (Vijayan et al 2003;Zhao et al 2009), but the concentrations used have not been as high as those used in this study. All growth and physiological parameters were significantly affected by salt stress.…”
Section: Discussionmentioning
confidence: 87%